Simone Wesner. Artists’ Voices in Cultural Policy: Careers, Myths and the Creative Profession after German Unification. Palgrave Macmillan, 2018. - Evelyn Preuss (Studies in 20th & 21st Century Literature, 2020)
Review of Simone Wesner. Artists’ Voices in Cultural Policy: Careers, Myths and the Creative Profession after German Unification. Palgrave Macmillan, 2018. xv + 197 pp.
Keywords: German literature; GDR; cultural policy